PENINGKATAN PENGETAHUAN KONSEP BILANGANMELALUI OBJEK LINGKUNGAN BELAJAR PADA ANAK - Elina, Seselia; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated Â cognitive of children in recognizing the concept of numbers.1) The child has not been able to call and show the symbol of the number 1-10, 2) The child has not been able to make a sequence of numbers 1-10 according to the object, 3) The child has not been able to connect the number with how to draw the line according to the number of objects. problem this study